Haematological malignancies: a guide to novel therapies. Issue 11 (15th December 2020) - Smith, Alistair; Milnthorpe, James
Abstract : The treatment of chronic haematological malignancies is advancing rapidly, with newer targeted therapies increasingly being used in place of conventional chemotherapy. This article provides a primary care guide to the use of novel therapies for chronic haematological malignancies, with a focus on chronic lymphocytic leukaemia (CLL) and chronic myeloid leukaemia (CML).